Peran Ekonomi Kreatif Dalam Meningkatkan Pendapatan Di Zaman Kopi Sengon Jombang - Febby Indah Oktavia; Lailatus Sa'adah (Universitas Hamzanwadi, 2022)
The purpose of this study is to understand the creative economic cycle in order to increase earnings in Zaman Kopi Sengon Jombang. The term